Response surface applied to mixtures of castor bean hull and presscake for organic fertilization of castor bean plants - Silva, Walciria Alves; Beltrão, Napoleão Esberard de Macêdo; dos Santos, José Wellingthon; Costa, Flavio Bezerra; Carvalho Junior, Genelicio Souza (Agrarian, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->Castor bean presscake and hull are the two sub-products resulting from the extraction of castor bean oil. Their use as organic fertilizers has aroused interest of producers who wish to aggregate value to these products and use them rationally. The growth of castor bean plants of the BRS Energia cultivar in substrates composed of mixtures of two organic materials (castor bean presscake and hull) associated to soil was evaluated in this paper. The experiment was carried out at the Embrapa Algodão greenhouse, in the city of Campina Grande, in Paraíba, Brazil, from February 2010 to June 2010. Five treatments with four replications were evaluated. The treatments were composed of soil, varying from 80 to 100%, and castor bean hull and presscake varying from 0 to 10%. In order to identify the best mixture to promote growth of the plants, the extreme-vertices experimental design was used in a simplex sub-region, due to the restrictions of some components of the mixture. The classification of the best mixture was made based on the following variables: plant height, leaf area, and total dry weight of the plant. These measurements were evaluated by mixture modeling, performed in the MATLAB® computer system. For all of the analyzed variables, the best mixture was composed of 10% of castor bean presscake, 10% of castor bean hull, and 80% of soil. <!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->